Magnetic Sphincter Augmentation After Gastric Surgery - Riva, Carlo Galdino (JSLS, 2019)
BACKGROUND: Persistent or de novo gastroesophageal reflux disease (GERD) may be a significant clinical issue after gastric/bariatric surgical procedures. We investigated the effect of magnetic sphincter augmentation (MSA) in the treatment of GERD after previous gastric/bariatric surgery. DATABASE: We conducted a systematic review according to the Preferred Reporting Items For Systematic Reviews and Meta-analyses statement. We searched multiple databases (PubMed, Cochrane, Embase, Scopus) up to May 2019. We also queried the prospectively collected database of patients who underwent MSA at our tertiary-care hospital and compared postsurgical to naïve patients operated during the same time period. RESULTS: Seven studies (3 case series and 4 case reports), for a total of 35 patients, met the inclusion criteria in the systematic review. The most common index operation was a bariatric procedure, either sleeve gastrectomy or Roux-en-Y gastric bypass. After MSA implant, the Gastroesophageal Reflux Disease–Health-Related Quality of Life (GERD-HRQL) score significantly improved compared to baseline (P = .005). Two patients (5.7%) required laparoscopic device removal. In the local institutional cohort series of 67 patients treated by MSA, the prevalence of preoperative grade B esophagitis, operative time, size of MSA, and length of stay were greater in patients with prior gastric surgery compared to naïve patients. CONCLUSIONS: MSA is a safe, simple, and standardized antireflux procedure. It is also feasible in patients with refractory GERD following gastric/bariatric surgery. Further prospective and comparative studies are needed to validate the preliminary clinical experience in this subset of patients.